IMPLEMENTASI KOMUNIKASI PEMASARAN TERPADU PADA YAYASAN NURUL IBAD JAKARTA TIMUR - Ruzqiyah Ulfa; Rustono Farady Marta (Universitas Bunda Mulia, 2016)
Study about Integrated Marketing Communication or IMC has become a common issues. Not just profit-oriented institutions, non-profit institutions also need to know the communication strategy of the